Molecular mechanisms of avian immunoglobulin gene diversification and prospect for industrial applications - Seo, Hidetaka; Hirota, Kouji; Ohta, Kunihiro (Frontiers in Immunology, 2024)
Poultry immunoglobulin genes undergo diversification through homologous recombination (HR) and somatic hypermutation (SHM). Most animals share a similar system in immunoglobulin diversification, with the rare exception that human and murine immunoglobulin genes diversify through V(D)J recombination. Poultry possesses only one functional variable gene for each immunoglobulin heavy (HC) and light chains (LC), with clusters of non-productive pseudogenes upstream. During the B cell development, the functional variable gene is overwritten by sequences from the pseudo-variable genes via a process known as gene conversion (GC), a kind of HR. Point mutations caused in the functional variable gene also contribute to immunoglobulin diversification. This review discusses the latest findings on the molecular mechanisms of antibody gene diversification in poultry, using chickens as a model. Additionally, it will outline how these basic research findings have recently been applied especially in the medical field. Deleted: This enhancement suggests potential for increased diversification of the immunoglobulin genes and facilitates the construction of a Deleted: ntibody Deleted: . From these libraries Deleted: chicken IgM Deleted: Deleted: . Deleted: s Deleted: generate antigen-specific monoclonal antibodies Deleted: have been Deleted: Since the antibodies generated by DT40 are chicken IgMs, humanization is necessary to reduce immunogenicity.